Environmental & architectural phenomenology. Vol. 25, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2014)
Vol. 25, No. 1, Winter 2014 (includes an entry honoring the memory of British-African novelist Doris Lessing, and essays by Stephen Wood Marco Cesario, Lena Hopsch, Rachel McCann & Jeff Malpas).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals